Peran Orang Tua dalam Menıngkatkan Keterampılan Membaca Bagı Peserta Dıdık dı SMP Islam Permata Hati Kabupaten Tangerang - Ummu Hani, Siti Hasna; Haerudin, Haerudin; Fitriani, Siti Hamsanah (Universitas Mathla'ul Anwar Banten, 2023)
The role of parents is very important in improving reading skills for students considering that children need the role of their parents more. This research aims to describe the role of parents in improving reading skills for class VII Ibnu Khaldun students at Permata Hati Islamic Middle School, Tangerang Regency and to describe the reading skills of class VII Ibnu Khaldun students at Permata Hati Islamic Middle School, Tangerang Regency. This type of research uses qualitative research with descriptive research methods. The subjects in this research were 5 parents of students, with data collection techniques through observation, interviews and documentation. This data analysis technique uses the Miles and Huberman analysis model consisting of data reduction, data presentation, and drawing conclusions. The results of this research show that (1) the role of parents in improving reading skills is by becoming a teacher for their children and providing a positive influence, (2) the reading ability of students at Permata Hati Islamic Middle School is based on the results of researchers' observations that were carried out in the parents of the students, and the five children studied by the researchers found that there was one child who was still not skilled in reading skills for junior high school age children and this was proven by the results of the Indonesian language report card which still got the standard KKM score of 78